2008
DOI: 10.1210/jc.2007-2724
|View full text |Cite
|
Sign up to set email alerts
|

High Adiponectin Concentrations Are Associated with the Metabolically Healthy Obese Phenotype

Abstract: Certain obese individuals have adiponectin levels similar to those found in normal BMI subjects; this is associated with the metabolically healthy obese phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
198
6
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(235 citation statements)
references
References 20 publications
19
198
6
12
Order By: Relevance
“…The diagnosis of MHO was obtained based on the joint combination of each obesity marker (BMI, waist circumference and body fat percentage) and six different sets of cardiometabolic abnormalities (Karelis et al, 2004;Meigs et al, 2006;Aguilar-Salinas et al, 2008;Wildman et al, 2008;Lynch et al, 2009) (Table 1). There were no exclusion criteria such as menopause, hormonal use and medications affecting metabolism, as well as diabetes and CVDs; participants were selected if they presented with overweight or obesity using the different anthropometric markers (BMI, waist or body fat).…”
Section: Determination Of the Prevalence Of Metabolically Healthy Obesementioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of MHO was obtained based on the joint combination of each obesity marker (BMI, waist circumference and body fat percentage) and six different sets of cardiometabolic abnormalities (Karelis et al, 2004;Meigs et al, 2006;Aguilar-Salinas et al, 2008;Wildman et al, 2008;Lynch et al, 2009) (Table 1). There were no exclusion criteria such as menopause, hormonal use and medications affecting metabolism, as well as diabetes and CVDs; participants were selected if they presented with overweight or obesity using the different anthropometric markers (BMI, waist or body fat).…”
Section: Determination Of the Prevalence Of Metabolically Healthy Obesementioning
confidence: 99%
“…There are currently no unique criteria for MHO, and several definitions have been proposed (Meigs et al, 2006;Aguilar-Salinas et al, 2008;Karelis, 2008;Wildman et al, 2008;Lynch et al, 2009). The criteria used to define MHO are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] However, clinical experience and well-documented studies in different populations indicate that metabolically benign, insulin-sensitive phenotypes are not infrequent within the obesity spectrum. 10,11 Adiponectin is the most abundant adipokine in the circulation and has insulin-sensitizing, anti-inflammatory and atheroprotective properties. 12 Associations of low plasma adiponectin levels with IR, components of the metabolic syndrome, the incidence of type 2 diabetes and increased cardiovascular risk, independent of established risk factors, have been shown repeatedly.…”
mentioning
confidence: 99%
“…Wildman and his colleagues in their study have reported that 51.3% of overweight and 31.7% of obese adults were MHO [9]. Others have reported a prevalence from 6% to 40% in different overweight and obese populations [11,20,22,23]. Data available from a limited number of studies from the West shows the prevalence of MHO ranging from 11-40% whereas the prevalence of MONW is about 5-45% [24].…”
Section: Prevalencementioning
confidence: 94%
“…It also limits the infiltration of monocytes/ macrophages into adipose tissue and their conversion into foam cells in the vessel wall providing the anti-inflammatory and antiatherogenic effects. Additionally, adiponectin also increases insulin sensitivity, fatty acid oxidation and decreases secretion of glucose from liver, increases glucose uptake, and adipogenesis [22,33,36]. Adiponectin also promotes glucose metabolism and accelerates the oxidation of free fatty acids in the muscle [37,38].…”
Section: Adiponectinmentioning
confidence: 99%